2006
DOI: 10.1253/circj.70.409
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Spasm and the Polymorphisms of the Endothelial Nitric Oxide Synthase Gene

Abstract: oronary spasm plays an important role in the pathogenesis of vasospastic angina. It may also contribute to the development of other acute coronary syndromes. [1][2][3][4] Acute myocardial infarction can occur at the site of atherosclerotic plaques that do not narrow the coronary artery lumen. 5 Plaque rupture followed by thrombosis, and vasoconstriction at the site of the plaque, are involved in coronary artery occlusion. 6,7 Coronary vasospasm has been suggested to occur as a result of reduced endotheliumdepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…In addition to an altered contractile response of coronary smooth muscle, impaired endothelial function, especially NO function, is associated with coronary vasospasm. 21,22 In the present study, we showed that endothelium-dependent FMD was decreased in vasospastic angina patients compared with control subjects, thus confirming the impaired vascular endothelial function in these patients and in agreement with previous reports. 11,12 Furthermore, of the 3 CCBs, only benidipine, a dihydropyridine, provided a significant improvement in endotheliumdependent FMD and plasma cGMP concentration in patients with coronary vasospasm.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to an altered contractile response of coronary smooth muscle, impaired endothelial function, especially NO function, is associated with coronary vasospasm. 21,22 In the present study, we showed that endothelium-dependent FMD was decreased in vasospastic angina patients compared with control subjects, thus confirming the impaired vascular endothelial function in these patients and in agreement with previous reports. 11,12 Furthermore, of the 3 CCBs, only benidipine, a dihydropyridine, provided a significant improvement in endotheliumdependent FMD and plasma cGMP concentration in patients with coronary vasospasm.…”
Section: Discussionsupporting
confidence: 93%
“…The precise mechanism of coronary spasm remains obscure, but endothelial dysfunction and smooth muscle hypercontraction have been reported as important factors. 12 Kaneda et al recently reported that polymorphisms of the endothelial nitric oxide synthase gene are associated with coronary artery spasm 13 and Mashiba et al reported that VA is influenced by polymorphism of the paraoxonase 1 gene A632G. 14 Racial differences in the angiographic patterns and prevalence of coronary spasm appear to exist between Asian and Caucasians, and the prevalence of VA appears to be higher in Asians than in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies have shown that Japanese ACS patients experience a higher incidence of coronary spasms than do Caucasians. 24,25) Although this racial difference may relate to differences in endothelial nitric oxide synthesis or autonomic nervous system activity, 25,26) the reason for this is not clear. Recent report suggests that coronary spasticity is related to airway hyper-responsiveness.…”
Section: Discussionmentioning
confidence: 99%